THE INFLUENCE OF PRICE, PLACE, PROMOTION, PROCESS, AND PHYSICAL EVIDENCE ON PRODUCT PURCHASE DECISIONS IN THE CREATIVE INDUSTRY (CASE STUDY ON OOAA PUZZLE) - Evan Tanadi; J.E. Sutanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The creative industry has shown promising growth within the last few decades globally and locally in Indonesia. However, the Covid-19 pandemic has presented major challenges for businesses in the industry. Most of the businesses in this industry have experienced significant loss of revenue as an impact of the crisis. Efforts are made to recover from the crisis, one of them is the implementation of digital infrastructure and technology. OOAA Puzzle as a part of the creative industry has implemented digitalization in its operations but is still facing marketing challenges that result in poor sales. Hence, this research is initiated in order to understand the influence of marketing mix on OOAA Puzzle’s customer purchase decision. This research is done by distributing questionnaires to 92 OOAA Puzzle’s customers as samples. The data is then analyzed using linear regression equation. This research concluded that price, place, promotion, process and physical evidence are influential to OOAA Puzzle’s customers' purchase decision. The result of data analysis shows that promotion is the most significant variable, followed by process, price, and lastly product, and physical evidence. These findings are then used as the basis of evaluation for this research’s subject to formulate an effective marketing mix strategy.